Care Workers and Managers' Experiences of Implementing Infection Control Guidance in an Epidemic Context: A Qualitative Study in the South East of England, during the COVID-19 Prevaccination Era. (3rd April 2023) - Bertini, Lavinia; Bogen-Johnston, Leanne; Sadhwani, Shanu; Middleton, Jo; Sharp, Rebecca; Wood, Wendy; Roland, Daniel; Forder, Julien; Cassell, Jackie A.
Abstract : The national response to COVID-19 has had a severe impact on adult social care settings, with high mortality amongst people receiving and providing care in England. Care workers had to rapidly adapt to new infection control measures to protect themselves, their colleagues, and the people receiving care. Infection control in residential and domiciliary care is always complex, but COVID-19 infection control measures impacted exceptionally on care workers' working and everyday lives. We undertook qualitative interviews with care workers and managers ( n = 10) in residential and domiciliary care for older people in the Southeast England during the first wave of the pandemic to understand their experiences, solutions, and concerns to implement guidance in practice. Data were analysed using framework analysis, and the following eight themes were identified: (1) Increasing visibility and support for the sector; (2) the impact of negative messaging about the sector; (3) feelings of isolation; (4) accessibility and usability of guidance; (5) social care staff as agents in producing and sharing good practice; (6) managing expectations and the impact of conflicting messages in the media; (7) improving communication with hospitals; and (8) problems in the early pandemic. The findings reveal widespread concerns for the marginalisation of the sector in the policy response and the inadequacy of infection control guidance. Guidance would benefit from a better understanding of domiciliary and residential care settings. This might involve the following steps: (a) coproduction of guidance with adult social care stakeholders, including those in direct-care roles and (b) a shift away from a clinical model of infection control towards a more flexible approach that attends to the inherent variability of care settings.